Improving Mathematical Problem-Solving Abilities by Virtual 5E Instructional Organization - Wannatida Yonwilad; Prasart Nuangchalerm; Parinya Ruangtip; Panadda Sangsrikaew (Journal of Educational Issues, 2024)
The purpose of this action research was to improve mathematical problem-solving abilities using the virtual 5E instructional organization for undergraduate math students who required to pass the criteria of 70% of the full score. This study involved thirty undergraduate math students from one university who were enrolled in mathematical problem-solving courses for mathematics teachers during the first semester of academic year 2021. They were randomly chosen using cluster random sampling. There are three types of tools utilized in this research: 1) a plan for mathematical problem-solving abilities, 2) an assessment of problem-solving abilities in mathematics, and 3) a student behavior observation form. The statistics used in the data analysis are descriptive for calculating mean, standard deviation, and percentage. The finding showed that mathematical problem-solving abilities had been achieved. Undergraduate students in mathematics had average scores of 35.00, 46.07, and 50.19 after completing learning activities in the first, second, and third cycle, indicating 58.33%, 76.78%, and 83.65%, respectively. In the second and third cycle, all students achieved 70% of the entire score. The findings shows that experienced undergraduate students can solve mathematical problems as a proportion of the overall score when using the virtual 5E instructional organization.